Organic substances as attractants for egg laying, Callosobruchur analis Fabr. on cowpeas (Vigna sinensis Endl.) - Bastos, José Alberto Magalhães (Pesquisa Agropecuaria Brasileira, 2014)
This is a study on the attraction of various organic substances to laying of eggs to Callosobruchus analis Fabr. The power of attraction for egg laying C. analis of the following organic substances were tested: cowpea seed meal (Vigna sinensis Endl), bean seed meal (Phaseolus vulgaris L.), corn starch, manihot starch, wheat meal, corn oil, peanut oil, cane sugar and corn meal. No attraction was evident. The laying capacity of 100 insects was tested by placing them in confinement with some cowpea meal. In 24 hours 380 eggs were deposited. The organic substances did not attract the egg laying.